Activation and pro-inflammatory cytokine production by unswitched memory B cells during SARS-CoV-2 infection - Castleman, Moriah J.; Santos, Adriana Luna; Lesteberg, Kelsey E.; Maloney, James P.; Janssen, William J.; Mould, Kara J.; Beckham, J. David; Pelanda, Roberta; Torres, Raul M. (Frontiers in Immunology, 2023)
Memory B cells are comprised of unswitched (CD27+IgD+) and switched (CD27+IgD-) subsets. The origin and function of unswitched human memory B cells is debated in the literature, whereas switched memory B cells are primed to respond to recurrent infection. Unswitched memory B cells have been described to be reduced in frequency with severe SARS-CoV2 infection and here we characterize their activation status, BCR functionality, and contribution to virally-induced cytokine production. Analyses of whole blood from healthy individuals, people immunized to SARS-CoV2, mild and severe SARS-CoV2 infection, confirm a reduction in the frequency of unswitched memory B cells during severe SARS-CoV2 infection and demonstrate this is reduction associated with increased levels of systemic TNFα. We further document severe viral infection is associated with an increased frequency of ‘IgD+’ only memory B cells that correlate with increased IgG autoantibody levels. Unswitched and switched memory B cells from severe SARS-CoV2 infection displayed evidence of heightened activation with concomitant reduction in expression of the inhibitory receptor CD72. Functionally, both populations of memory B cells from severe SARS-COV2 infection harbored a signaling competent BCR that displayed enhanced BCR signaling activity in the unswitched population. Finally, we demonstrate that B cells from mild SARS-CoV2 infection are poised to secrete pro-inflammatory cytokines IL-6 and TNFα. Importantly, unswitched memory B cells were a major producer of IL-6 and switched memory B cells were a major producer of TNFα in response to viral TLR ligands. Together these data indicate that B cells contribute to the inflammatory milieu during viral infection.